Gestão da mudança educacional nas escolas da Inspetoria Madre Mazzarello - Machado, José Ronaipe das Neves (2020)
This qualitative research presents as its central goal the analysis of the educational change process management accomplished by the schools within the Inspetoria Madre Mazzarello. The research intends to deepen the knowledge regarding the processes and dynamisms that bring about efficacy and success to an education change process. The data interpretation and analysis were carried about upon the establishiment of the analysis categories, which were inductively developed, and its theoretical referential was the educational change process literature. Data were gathered upon open interviews and quiestionaires adhibition. Data were analyzed based on the Content Analyiss theoretic-methodological approach and premises, as well as on its tecniques, applying the support, resources and tools of computer softwares in order to treat and organize the same data. Analysis resulted in the establishement of six categories, which made it possible to proceed to data interpretation: communication management, organizational management, pedagogical management, change theory and meaning, stages of change process, and actors involved in the change process. Each analysis category contributed to understand and identify the factors tha affected the educational change process management within the Inspetoria Madre Mazzarello, emphasizing how respondents identify the factors that positively affected the Effective Practice Project and how they concurred to its success. Those factors are related to: the attention to the communicational process in order to achieve adhesion, engagement, and commitment; necessity of contextualizing the proposal to each school reality; the centrality of pedagogical related issues, including the teaching and learning process, teachers training, support and follow-up, and leadership commitment; the attention to the way upon which people elaborate meaning and develop an implicit change theory; the organization and understanding of the change process, accordingly to the demands and challenges inherents to each stage comprised in the same process, that is, initiation, implementation, and institutionalization; the demand to promote the envolvement of the multiple groups of people who are envolved with the change process.